2017
DOI: 10.2147/ott.s141968
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microwave ablation and hepatic resection for hepatocellular carcinoma: a meta-analysis

Abstract: Background and aimsHepatic resection (HRN) and microwave ablation (MWA) have significant advantages in treating hepatocellular carcinoma; however, it remains unclear which way produces better outcomes. This meta-analysis of cohort studies compared the treatments in terms of effectiveness and safety.MethodsSix electronic databases (PubMed, Medline, EMBASE, Web of Science, EBSCO, and The Cochrane Library) were retrieved for studies comparing MWA and HRN. The meta-analysis was conducted based on statement of pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 26 publications
(18 reference statements)
2
39
1
Order By: Relevance
“…For microwave ablation, recent studies have concentrated on the efficacy of microwave ablation compared with RFA and hepatic resection. A recent meta-analysis showed that microwave ablation may be superior to hepatic resection as it is as effective as hepatic resection in terms of overall survival, disease-free survival, tumor recurrence and is associated with fewer complications [55], while microwave ablation is better than RFA in preventing LTP in treating large tumors [5,56]. In our network meta-analysis, we demonstrated that microwave ablation also performed well in regard to LTP.…”
Section: Discussionsupporting
confidence: 51%
“…For microwave ablation, recent studies have concentrated on the efficacy of microwave ablation compared with RFA and hepatic resection. A recent meta-analysis showed that microwave ablation may be superior to hepatic resection as it is as effective as hepatic resection in terms of overall survival, disease-free survival, tumor recurrence and is associated with fewer complications [55], while microwave ablation is better than RFA in preventing LTP in treating large tumors [5,56]. In our network meta-analysis, we demonstrated that microwave ablation also performed well in regard to LTP.…”
Section: Discussionsupporting
confidence: 51%
“…Recent meta-analyses of MWA with RFA for the treatment of liver cancer reported that MWA was at least as safe and effective as RFA [8, 9]. The Zhang et al meta-analysis of nine hepatocellular carcinoma (HCC) studies showed that there were no differences between MWA and HR for recurrence, overall survival, and disease-free survival [10]. However, they showed that MWA was significantly favored over HR for operative time and blood loss, as well as complications [10].…”
Section: Introductionmentioning
confidence: 99%
“…The Zhang et al meta-analysis of nine hepatocellular carcinoma (HCC) studies showed that there were no differences between MWA and HR for recurrence, overall survival, and disease-free survival [10]. However, they showed that MWA was significantly favored over HR for operative time and blood loss, as well as complications [10]. Several studies have been published recently that were not included in the Zhang et al meta-analysis, including those which compared HR and MWA in metastatic liver cancer [3, 4, 7, 1117].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ablation of primary and secondary liver tumours is a potentially curative treatment, and an alternative for patients not eligible for surgical resection due to severe comorbidity or underlying liver disease. Its efficacy has been proven for tumours smaller than 30mm in diameter, especially in treatment of hepatocellular carcinomas 1 . Adequate imaging of the tumour and precise guidance of the ablation device are crucial for accurate local ablative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate imaging of the tumour and precise guidance of the ablation device are crucial for accurate local ablative treatment. Accurate targeting is essential for an effective treatment, reducing the risk for local recurrence and need of retreatment 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%